Matrix metalloproteinase-8 (MMP-8) and its inhibitors: A minireview - Sandip Kumar Baidya; Suvankar Banerjee; Sujay Guti; Tarun Jha; Nilanjan Adhikari (Elsevier, 2024)
The type-II collagenase, also known as matrix metalloproteinase-8 (MMP-8) plays a vital role in a variety of physiological illnesses namely cardiovascular, musculoskeletal, renal, digestive, and respiratory ailments including cancer. However, numerous novel compounds with effective MMP-8 inhibitory activity have been created by research and academic institutions, pharmaceutical companies, and both. Sadly, despite showing promising results, these compounds have a variety of negative side effects. In this context, a number of MMP-8 inhibitors having potential inhibitory activity with different key structural features such as hydroxamates, carboxylic acid, thiol and mercaptosulfide, phosphonate, and pyrimidine-2,4,6-trione have been discussed. Additionally, various ligand-based and structure-based drug designs that have been previously conducted on a variety of MMP-8 inhibitors have been thoroughly reviewed and that can offer important information regarding the development of novel MMP-8 inhibitors in the future. Therefore, the detailed knowledge about the key structural features of the existing MMP-8 inhibitors can be found, and further with the help of drug design strategies, a novel class of collagenase inhibitors may be identified. In light of this, this work may be beneficial for researchers looking into the processes involved in developing and identifying new potential and promising MMP-8 inhibitors.